Prevalence of Typhoid Osteomyelitis among Young Adults in Sheikh Khalifa bin Zayed Hospital Quetta: A Cross-Sectional Study - Khan, Ezhar Ahmed; Wali, Ahmed; Mehmood, Tariq; Adil, Mohammad; Anwar, Muhammad; Khan, Hafiz Yaseen; Amin Ullah,; Saleem, Irfan (Indus Journal of Bioscience Research, 2025)
Background: Typhoid fever, caused by Salmonella enterica serovar Typhi, continues to be a problem for public health in low- and middle-income countries, among them Pakistan. There are many cases of systemic and gastrointestinal complications, but in contrast, young adults face a rare, life-threatening complication of osteomyelitis from S. Typhi, which is often unreported. Objective: The objective of this study is to find the prevalence of typhoid-related osteomyelitis among young adults at Adults in Sheikh Khalifa bin Zayed Hospital, Quetta Pakistan. Methods: The research study was conducted between September 2024 and February 2025 in Sheikh Khalifa bin Zayed Hospital, Quetta. We used a structured form to assess those young adults with typhoid fever who might have bone involvement. For confirmation, we did blood tests, imaging scans (MRI and CT), bone cultures, and tests using the Widal and Typhidot methods. We collected the data through consecutive sampling. The study’s key finding was the rate of typhoid osteomyelitis in those with radiologic or microbiologic bone involvement during their typhoid illness. Results: Out of 100 young adults with laboratory-confirmed typhoid fever, 2 people (2%) had typhoid osteomyelitis; one had it in the femur and the other in the tibia. ESR, CRP, and positive imaging and culture were found in both patients who exhibited fever and localized bone pain. Patients were managed with antibiotics via the IV and by mouth, and in one case, surgical drainage was also provided. All symptoms in both patients disappeared as they recovered. Conclusion: Although it is uncommon (occurring in 2% of cases), typhoid osteomyelitis is difficult to diagnose and can affect even healthy young adults. Early diagnosis with appropriate imaging is crucial in areas where tuberculosis is prevalent and resources are scarce. These results suggest that doctors need to look more closely for infections and try to prevent illnesses by endorsing vaccination.